2018
DOI: 10.1002/cncr.31293
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of avelumab in patients with advanced solid tumors: A pooled analysis of data from the phase 1 JAVELIN solid tumor and phase 2 JAVELIN Merkel 200 clinical trials

Abstract: BACKGROUNDAntibodies targeting the programmed death‐ligand 1 (PD‐L1)/programmed cell death protein 1 (PD‐1) checkpoint may cause adverse events (AEs) that are linked to the mechanism of action of this therapeutic class and unique from those observed with conventional chemotherapy.METHODSPatients with advanced solid tumors who were enrolled in the phase 1 JAVELIN Solid Tumor (1650 patients) and phase 2 JAVELIN Merkel 200 (88 patients) trials received avelumab, a human anti–PD‐L1 IgG1 antibody at a dose of 10 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
1
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 32 publications
9
62
1
3
Order By: Relevance
“…In the initial dose‐escalation part (phase Ia), patients with various tumors received avelumab at 1, 3, 10, or 20 mg/kg q2w via a 1‐hour intravenous infusion . In the dose‐expansion part (phase Ib), patients were enrolled into tumor‐specific cohorts and received avelumab at 10 mg/kg q2w …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial dose‐escalation part (phase Ia), patients with various tumors received avelumab at 1, 3, 10, or 20 mg/kg q2w via a 1‐hour intravenous infusion . In the dose‐expansion part (phase Ib), patients were enrolled into tumor‐specific cohorts and received avelumab at 10 mg/kg q2w …”
Section: Methodsmentioning
confidence: 99%
“…12 In the dose-expansion part (phase Ib), patients were enrolled into tumor-specific cohorts and received avelumab at 10 mg/kg q2w. 11,31 JAVELIN Solid Tumor JPN is a phase I, open-label, multicenter trial of avelumab in Japanese patients with various advanced or metastatic solid tumors. In the initial dose-escalation part, patients received avelumab at 3, 10, or 20 mg/kg q2w.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Pooled safety data on avelumab reported that 25% of patients experienced anygrade infusion reactions (439/1,738) with high-grade events in 0.7% (12/1,738); most occurred during the first infusion, with nearly all reactions occurring within the first 4 treatment cycles. 128,129 Premedication appeared to decrease the rate of severe infusion-related reactions. 128 The U.S. prescribing instructions for avelumab include acetaminophen and diphenhydramine before infusion during the first 4 treatment cycles.…”
Section: Infusion-related Reactionsmentioning
confidence: 99%
“…128,129 Premedication appeared to decrease the rate of severe infusion-related reactions. 128 The U.S. prescribing instructions for avelumab include acetaminophen and diphenhydramine before infusion during the first 4 treatment cycles. 129 Most infusion reactions associated with ICIs are mild and associated with low-grade fever, chills, headache, or nausea.…”
Section: Infusion-related Reactionsmentioning
confidence: 99%
“…Recent studies suggest that pneumonitis after PD-L1 inhibitor therapy may occur less frequently than after PD-1 inhibitor therapy. For example, in a pooled analysis of data from phase 1 and phase II trials, the overall incidence of anygrade pneumonitis for avelumab in patients with advanced solid tumors was around 1.2% [131]. Similarly, Pillai et al and Khunger et al both reported that the incidence of any-grade pneumonitis was higher in NSCLC patients treated with PD-1 inhibitors as compared to PD-L1 inhibitors (PD-1 vs PD-L1: around 4% vs around 2%) [83,127].…”
Section: Pd-1 and Pd-l1 Inhibitorsmentioning
confidence: 99%